If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x * 12 = 3x * 2 Reorder the terms for easier multiplication: 3 * 12x = 3x * 2 Multiply 3 * 12 36x = 3x * 2 Reorder the terms for easier multiplication: 36x = 3 * 2x Multiply 3 * 2 36x = 6x Solving 36x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 36x + -6x = 6x + -6x Combine like terms: 36x + -6x = 30x 30x = 6x + -6x Combine like terms: 6x + -6x = 0 30x = 0 Divide each side by '30'. x = 0.0 Simplifying x = 0.0
| 6.99x+0.55=11.94 | | 5x^2+3y^2-8=0 | | X+0.07x=50 | | 3x+16=6x+198 | | 8x-4+6x+15=14x+11 | | 20/-d=13 | | 17+d=20 | | 14+4a=a+4-8 | | x+y(4)=120 | | 1+2n=-10+5-n+4n | | J-1.2(.4-.1j)=2.88 | | 0.4x=60 | | Bx+9=3y | | 5y+20=7x-56 | | x/5-7/4=x/10-1/20 | | -6n-5n=-16-7n | | 9/22=x/176 | | Ar=3r+14 | | 34=x/64 | | 63-f=52 | | K-8=5k-k-5 | | .2I+4(.3+.2I)=2.2 | | 14x+2=9x+20 | | 0.1x+0.2x=6 | | -(12-t)+(2t-4)= | | 17*v/v=7 | | 13/21=x/147 | | 6(x+9)=60 | | 1+2r-r=11+3r | | 12*c=156 | | 4y=-6+4x | | 1+1+5x-8=5x+x |